Cross Cultural Pragmatics: Compliment Response Strategy Used on the British and Indonesian Talk show - Fitri Ana Rahmayani (Institut Agama Islam Negeri Palopo, 2020)
This research aims at comparing the pattern of compliment response strategy used by two different cultures between British’s and Indonesia’s talk show. The method used is descriptive qualitative research. The data is taken from “Loose Women” (British Talk Show) and “Tonight Show” (Indonesian Talk Show). The data collections are done as follows: first, download the video of “Tonight Show” and “Loose Women”. Second, observed both videos and then compared the video. The last transcribed the compliment response and then choose the pattern of compliment response strategy based on the theory of (R. Herbert, 1989) to be analyzed further. The result shows that strategy of no acknowledgment gets a higher percentage in “Tonight Show” that is (31.03%), this strategy as the first usage in the compliment response strategy, disagreement strategy gets (23.07%) and as the second usage in the compliment response strategy, the third usage is appreciation token strategy (17.24%) in responding the compliment. Meanwhile, the Talk Show entitled “Loose Women” (British Talkshow), the higher strategy is comment acceptance (28%), appreciation token, return, and no acknowledgement strategy(16%). It can be concluded that the most prominent used in both Talk show are no acknowledgement strategy and comment acceptance strategy. Those both strategies is included rejection pattern in responding the compliment. In this case, British tends to receive the praise and respond to what was discussed and even they provide additional information with the intention of keeping the communication going, it means that they are open in responding to what was discussed, but that contrasts with Indonesia culture, Indonesian people intended to humble themselves and minimize the things commented on praise as an expression of humility. It means that they do not want to be seen as an arrogant artist or public figure. They only want to keep their image as an artist.